Diagnostic videolaparoscopy in gynecology - Bendezú Martínez, Guido (2015)
OBJECTIVE: To establish the most common gynecological pathology diagnosed by video laparoscopy. MATERIALS AND METHODS: Of the approximately 253 diagnostic videolaparoscopias made in the "Felix Gutierrez Torrealva" EsSalud, Ica Hospital between March 1996 and July 2004, 236 cases were evaluated. RESULTS: Of the 236 interventions evaluated, 125 (52.9%) were for infertility, 32 (13.6%) for chronic pelvic pain, 31 (13.1%) for ovarian cyst, 31 (13.1%) for tubal blockages in May (2.1%) for ectopic pregnancy. Mainly operative findings were: 42 (17.8%) cases of adherence syndrome, 42 (17.8%) of polycystic ovarian disease, 41 (17.4%) of endometriosis, 40 (16.9%) for pelvic inflammatory disease Chronic, 32 (13.6%) of leiomyomatosis and tubal occlusion, 32 (13.6%) of hydrosalpinx. The type of anesthesia administered was mainly spinal and inhalation general, the average hospital stay was 2 days; the complications were minimal and referred to posraquídea 8 cases of headache, 7, wound infection, 7 urinary tract infection; 6 cases were converted to laparotomy. Antibiotics and analgesics was prophylactically. CONCLUSION: The most frequent gynecological pathology found by videolaparoscopy consisted adherence syndrome, polycystic ovary syndrome, endometriosis and chronic pelvic inflammatory disease.